2014
DOI: 10.1111/sms.12225
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing isometric exercise training‐induced reductions in resting blood pressure

Abstract: Hypertension is a major health concern, and current recommendations for blood pressure management (lifestyle modifications and pharmacological intervention) have not been universally successful. For two decades, isometric exercise training (IET) has become established as effective at reducing in resting BP (RBP) in a short period (4-10 weeks). The most common IET modes have comprised isometric handgrip (IHG) or isometric bilateral leg (IBL) training and 4 × 2-min contractions at ∼20-50% maximal voluntary contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 94 publications
(298 reference statements)
0
15
0
1
Order By: Relevance
“…One type of exercise, which has gained support in health studies in the recent decades, is resistance training (RT), which is based on efforts made against a specific resistance and aims to increase power, strength and/or muscle endurance over time 2,9 . In addition, some studies have shown significant reductions in resting blood pressure (BP) after dynamic and isometric RT, and have suggested that four weeks of RT may contribute to the treatment and / or prevention of SAH 11,12,13 . Suggesting that isometric RT may have a potential for the largest reductions in BP 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…One type of exercise, which has gained support in health studies in the recent decades, is resistance training (RT), which is based on efforts made against a specific resistance and aims to increase power, strength and/or muscle endurance over time 2,9 . In addition, some studies have shown significant reductions in resting blood pressure (BP) after dynamic and isometric RT, and have suggested that four weeks of RT may contribute to the treatment and / or prevention of SAH 11,12,13 . Suggesting that isometric RT may have a potential for the largest reductions in BP 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Its use has been supported by different meta-analyses 11,13 , and was recently included in important scientific statements as a promising useful tool in the management of BP. In which mechanisms that result in possible decreases in BP after intervention include neural (sympatho-vagal activity), vascular (endothelial function) and inflammatory adaptations 12,14 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations